Characteristics and quality of life of nine-year survivors with metastatic melanoma treated with pembrolizumab beyond second-line therapy - Dugas-Breit, S.; Forschner, A.; Erdmann, Michael; Gutzmer, R.; Kähler, K. C.; Holst, I.; Brekner, A.; Franklin, C.; Sindrilaru, A.; Zimmer, L.; Heinzerling, Lucie; Utikal, J.; et al. (European Journal of Cancer, 2026)
Background Immune checkpoint blockers have improved survival in metastatic melanoma. Long-term quality of life (QoL) and sequelae from immune-related adverse events (irAE) are therefore of increasing importance. This study reports long-term outcomes from a real-world cohort of patients with stage IV melanoma treated with pembrolizumab after progression on ipilimumab and, if indicated, BRAF/MEK inhibition. Methods Survival of patients who started treatment with pembrolizumab within the German Expanded Access Program (EAP) were evaluated in Cancer centers that included ≥ 10 patients. For survivors, baseline characteristics, best response and irAEs were assessed retrospectively. In addition, in a cross-sectional approach patients were interviewed for persisting symptoms and QoL (WHO-5, EORTC QLQ-C30). Results Of 325 treated patients, 55 (17 %) survived after a median follow-up of 9.1 years. At treatment start, survivors had a median age of 60 years; 60 % were male; 40 % BRAF-mutated; 66 % stage M1c/d. Overall response rate was 89 %, including 69 % complete responses. Progression occurred in 22 (40 %). As of May 2024, 46 (84 %) were disease-free, 7 (13 %) had controlled disease, and 2 (4 %) progressed. IrAEs occurred in 39 (71 %), with 15 (27 %) grade 3/4. Persisting symptoms were reported by 19 (35 %), mainly endocrine insufficiencies, vitiligo, and fatigue. Median WHO-5 score was 76 %, and mean QLQ-C30 global health 70.1. Survivors with prior irAEs had significantly lower QoL (WHO-5, p = 0.026) and social functioning (QLQ-C30, p = 0.046). Of 21 survivors < 65 years (38 %), 11 (20 %) were employed at follow-up. Conclusion Pembrolizumab induced long-term survival in a real-world pretreated melanoma cohort. Despite persisting symptoms in one third, QoL, when measured by standard instruments, was good for most survivors nearly a decade after treatment.
CRIS-Team Scopus Importer:2025-12-19
Keywords: Long-term survival; Long-term toxicity; Melanoma; Pembrolizumab; Quality of life